2015
DOI: 10.1097/mao.0000000000000619
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss Is Associated With Decreased Nonverbal Intelligence in Rural Nepal

Abstract: Objective Evaluate the association between adolescent and young adult hearing loss and nonverbal intelligence in rural Nepal Study Design Cross-sectional assessment of hearing loss among a population cohort of adolescents and young adults Setting Sarlahi District, southern Nepal Patients 764 individuals aged 14–23 years Intervention Evaluation of hearing loss, defined by WHO criteria of pure-tone average (PTA) >25 decibels (0.5, 1, 2, 4 kHz), unilaterally and bilaterally Main Outcome Measure Nonverba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, most research was conducted in school-aged children 23,24 and adolescents. 25,26 Martinez-Cruz et al 23 showed that children with unilateral severe to profound sensorineural hearing loss had significantly lower intelligence coefficients than healthy children. Emmett et al 26 reported that hearing loss in adolescents and young adults would be associated with decreased nonverbal intelligence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most research was conducted in school-aged children 23,24 and adolescents. 25,26 Martinez-Cruz et al 23 showed that children with unilateral severe to profound sensorineural hearing loss had significantly lower intelligence coefficients than healthy children. Emmett et al 26 reported that hearing loss in adolescents and young adults would be associated with decreased nonverbal intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Martinez-Cruz et al 23 showed that children with unilateral severe to profound sensorineural hearing loss had significantly lower intelligence coefficients than healthy children. Emmett et al 26 reported that hearing loss in adolescents and young adults would be associated with decreased nonverbal intelligence. Academic achievement of children with severe to profound hearing loss was significantly impaired relative to peers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the early life stressors that led to stunting may have impaired attention, motivation, memory, or a combination of these factors (Aburto, Ramirez‐Zea, Neufeld, & Flores‐Ayala, ; Baker‐Henningham, Hamadani, Huda, & Grantham‐McGregor, ; Chang, Walker, Grantham‐McGregor, & Powell, ; Fernald & Grantham‐McGregor, ; Gardner, Grantham‐McGregor, & Himes, ). We also lacked information on vision and hearing loss in our cohorts, which would have hampered children's ability to accumulate human capital (Chua & Mitchell, ; Davis & Hind, ; Emmett et al, ; Lim et al, ; Sharma et al, ; Steward‐Brown, Haslum, & Butler, ; Teasdale & Sorensen, ). This did not bias our estimates of the associations between stunting and the outcomes that we considered, but understanding the pathways would be useful for directly addressing the underlying human capital deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Nonverbal intelligence measures have been shown to be important predictors of positive language outcomes in deaf children with cochlear implants (Cejas et al, 2018; Dawson et al, 2002; Meinzen-Derr et al, 2010; Phillips et al, 2014; Surowiecki et al, 2002). In addition, nonverbal intelligence was shown to be adversely affected by bilateral hearing loss, for instance (Emmett et al, 2015).…”
Section: Methodsmentioning
confidence: 99%